Evaluation of HELLP syndrome in pregnancy induced hypertension- a study of 60 cases in a tertiary level hospital (Journal of Dhaka National Medical College & Hospital, 2015)
Objective:HELLP syndrome is a serious complication in the latter part of pregnancy. Sometimes, hypertension may accompanied with HELLP syndrome. The aim of this study is to determine the proportion of HELLP syndrome occurs in pregnancy induced hypertension.Method: A prospective study was conducted among 60 patients by nonrandomized sampling came after 20 weeks of gestational age with sustained rise of blood pressure 140/90mmHg irrespective of age. After admission in the Institute of Child and Mother Health(ICMH), Matuail, Dhaka, proper history & physical examination were carried out and relevant investigations were done. Appropriate and up to date management were applied to the sick mothers. Results: HELLP syndrome were demonstrated in 3(5%) patients out of sixty. Of them one(33.34%) mother died within six hour after delivery and two(66.66%) habies were born stillbirth. Conclusion: Early diagnosis and meticulous management can save the mother and her baby who suffered from HELLP syndrome.J. Dhaka National Med. Coll. Hos. 2015; 21 (02): 6-9